All-weather anti-salt solar desalination using a sandwich evaporator with thermal storage and asymmetric wettability - Yimin Qu; Changliang Lu; Ziyue Zhang; Xi Wen; Xuanli Jing; Tiaohong Zhang; Ting Lv; Dajian Huang; Yanping Wang; Xiaohu Qiang (Chemical Engineering Journal, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Inflammation-targeted bioactive SiMo glass-ceramic nanozymes for adaptive and sequential infection-impaired wound repair through precise immunoregulation and antiinfection - Jing Tian; Yanzi Zhao; Yanping Zuo; Xiaochen Su; Long Zhang; Weipeng Qiang; Zuhao Zhang; Minhui Ai; Houjin Zhuang; Qian Huang; Meng Luo; Bo Lei (Chemical Engineering Journal, 2026)

Cooling load forecasting for urban district cooling systems using a hybrid multi-scale deep learning approach - Chao Zeng; Yang Feng; Haixia Cao; Jing Wang; Yanping Yuan (Energy and Buildings, 2026)

Sustained activation of peracetic acid by hydroxylamine and ferrous irons for enhanced short-chain fatty acids production from sludge fermentation - Guilin Ma; Yanping Zhang; Jing Zhang; Kun Yang; Shuyu Yang (Journal of Water Process Engineering, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

A Study on the Species Diversity, Mating Types, and Clinical Relevance of Trichophyton mentagrophytes/interdigitale Complex Infections in Guizhou Province - Wei Hu; Kexin Xu; Jing Zhou; Wanglan Luo; Songgan Jia; Xiangyu Liu; Zhengling Shang; Yinhui Jiang; Zhi Liu; Yanping Jiang (Mycopathologia, 2026)

Adaptive VP1 sites 93 and 97 modulate antigenic evolution and receptor binding of Senecavirus A: Phylogenetic analysis and validation with recombinant viruses - Jing Yang; Zhiliang Zhang; Weijia Sha; Mingyue Peng; Yize Li; Xiaoyu Ge; Jiaxuan Li; Wen Cui; Yanping Jiang; Xiaona Wang; Lijie Tang (Veterinary Microbiology, 2026)

Surface reflectance in homogeneous regions follows a Gamma distribution: principles, validation and applications - Yuanhong Liao; Yuqi Bai; Yanping You; Jie Wang; Shuang Chen; Ming Lin; Jin Chen; Jing M. Chen; Bing Xu; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Intraspecific Variations and Characteristics of Clinical, Physiological, and Antifungal Susceptibility Profiles of Trichophyton rubrum in Southwest China - Yanni Deng; Wanglan Luo; Hao Hu; Jing Zhou; Qian Zhang; Songgan Jia; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Molecular Epidemiology, Mating Types, Clinical, and Physiological traits of Microsporum canis in Humans and Companion Animals (Cats and Dogs) in the Guiyang Region, Southwest China - Hao Hu; Bin Jiao; Yanni Deng; Wanglan Luo; Jing Zhou; Wei Lei; Zhengling Shang; Yinhui Jiang; Zhengrong Wang; Zhu Zeng; Yanping Jiang (Mycopathologia, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Unvegetated Tidal Flats: A Critical Yet Vulnerable Coastal Blue Carbon Sink - Yanping Wang; Changchun Li; Zhaoliang Peng; Jing Luo; Senlin Zhu; Yumeng Sun; Ruping Liu; Dongcheng Jiang; Xiangqian Zhou; Faming Wang (Global Change Biology, 2026)
Unvegetated tidal flats, despite accounting for approximately 24.9% of global blue carbon ecosystem area, remain underrepresented in blue carbon budgets. Here, we synthesize data from 184 sites across 23 countries to quantify their carbon stocks, carbon accumulation rate (CAR) and greenhouse gas (GHG, CO 2 and CH 4 ) emissions. Our results reveal that tidal flats sequester 8.6 (4.5–9.9) Tg C yr −1 and store 1.2 (0.7–2.0) Pg C in the top meter of sediments, increasing global blue carbon estimates by 6%–17%. However, they simultaneously emit 0.073 Tg CH 4 yr −1 (3.3 Tg CO 2 eq yr −1 ), 27.9% of the CH 4 emissions from salt marshes, offsetting 14.1% (1.8%–20.4%) of their carbon sequestration benefits. Mudflats exhibit the highest carbon stocks and CO 2 fluxes among different sediment types, primarily due to their abundant binding sites of fine‐grained particles and stronger microbial activities. Both CAR and CH 4 fluxes decline poleward, with tropical zone as hotspots. Our findings highlight the urgency of integrating tidal flats into climate mitigation strategies, particularly given their vulnerability to land‐use changes and sea‐level rise. Conservation efforts must balance carbon sequestration gains against CH 4 trade‐offs to optimize their climate regulation potential.

Improvement of electron transfer via anthraquinone-2-sulfonate addition to enhance volatile fatty acids production in anaerobic digestion system - Xiaoyue Li; Tingting Jiang; Huiyan Jing; Yue Cui; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2025)

Hydroxylamine enhanced Fe(Ⅱ)-activated peracetic acid process to promote short-chain fatty acid production during sludge anaerobic fermentation - Jing Zhang; Yanping Zhang; Junliang Dong; Fen Li; Zhenjie Guo; Yibing Li (Journal of Environmental Chemical Engineering, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Unraveling the alkaloid diversity and pharmacological potential of Ocimum: Integrated UPLC-MS/MS, network pharmacology, and transcriptomic insights for functional food and drug discovery - Jingtian Yang; Jing Yuan; Mengling Yu; Yanping Mao; Mei Liu; Lingliang Guan; Lei Liu (Food Research International, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Synergistic bioaugmentation: Serratia sp. WKD and carboxymethyl cellulose-modified nano-zero-valent iron enhance malachite green decolorization by activated sludge - Linna Du; Xinjiao Dong; Huan Wu; Gang Li; Jiacheng Zhou; Yiqing Wu; Yanping Xiao; Jing Qin; Xiu Wang (Journal of Water Process Engineering, 2025)

Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Jamie Bojko; James Becnel; Edouard Bessette; Sam Edwards; Jing Gao; Wei-Fone Huang; Nataša Katanić; Amjad Khalaf; Tian Li; Jonathan W. Snow; Leellen F. Solter; Cheyenne E. Stratton; et al. (Journal of Invertebrate Pathology, 2025)

Titanium dioxide nanoparticles disturb glucose homeostasis in association with impaired enteroendocrine cell differentiation - Kai Zou; Linna Du; Jing Qin; Jiacheng Zhou; Yanping Xiao; Xixi Song; Hongxia Liu; Xiu Wang (Food and Chemical Toxicology, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Effects of Fe3O4 on production of even-carbon volatile fatty acids by anaerobic fermentation of kitchen waste under ultrasonic-alkali pretreatment: Performance, metabolic functions, and metabolic pathways - Ziang Wang; Rufei Liu; Yue Cui; Zhihan Zhang; Huiyan Jing; Zhiling Chen; Shen Tian; Ziyi Yang; Yanping Liu (Journal of Environmental Chemical Engineering, 2025)

Research on PWV fusion based on ERA5 PWV and FY-4A PWV in Chinese mainland - Wei Du; Yong Wang; Xiao Liu; Jing Huang; Yanping Liu; Xiangshun Meng (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Comprehensive lipid profiling and metabolic pathway analysis of Ocimum: Unveiling key variations and regulatory mechanisms for breeding and metabolic exploration - Jingtian Yang; Chengting Zhang; Mengling Yu; Jing Yuan; Yanping Mao; Mei Liu; Lei Liu; Lingliang Guan (Food Bioscience, 2025)

Research on the impact of the belt and road initiative on the carbon emission performance of countries along the route - Jing Li; Yanping Zhou; Huiying Chen (Environment, Development and Sustainability, 2025)

Microtopography-induced hydrological heterogeneity promotes the co-assembly of vascular plant and biocrust communities, providing synergistic protective functions for the Great Wall - Yanping Liu; Wanfu Wang; Jing Ren; Yanhong Gao; Fasi Wu; Yafei Shi; Hongtao Zhan; Chengxu Chi; Rongliang Jia (Science of The Total Environment, 2025)

Salicylic acid cooperates with different small molecules to control biotic and abiotic stress responses - Kexing Xin; Yining Wu; Aziz Ul Ikram; Yanping Jing; Shan Liu; Yawen Zhang; Jian Chen (Journal of Plant Physiology, 2025)

Bisulfite-free detection of DNA methylation in early-stage lung cancer with a multiplex SERS immunoassay - Dechan Lu; Yanping Chen; Longfeng Ke; Zufang Huang; Yudong Lu; Jing Wang (Chemical Engineering Journal, 2025)

Two paths, one goal: mechanism of calcium homeostasis to balance plant growth and immunity - Aziz Ul Ikram; Yanping Jing; Huan Chen; Jian Chen (Science China Life Sciences, 2025)

Novel advanced oxidation technology of Fe2+-activated peracetic acid for high efficient disintegration of waste activated sludge - Wenqi Liu; Yanping Zhang; Jing Zhang; Ning Lv; Yibing Li (Journal of Environmental Chemical Engineering, 2024)

Promotional effect of microwave radiation treatment on the desorption of CO2 from mono-ethanolamine (MEA) solution over FeOOH catalyst - Haoran Zhang; Junge Lv; Zhibo Xiong; Huancong Shi; Jing Jin; Mengqi Liu; Yanping Du; Wei Lu (Journal of Environmental Chemical Engineering, 2024)

Vascular plants and biocrusts ameliorate soil properties serving to increase the stability of the Great Wall of China - Yanping Liu; Jing Ren; Wanfu Wang; Yafei Shi; Yanhong Gao; Hongtao Zhan; Yayong Luo; Rongliang Jia (Science of The Total Environment, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Electrochemistry promotion of Fe(Ⅲ)/Fe(Ⅱ) cycle for continuous activation of PAA for sludge disintegration: Performance and mechanism - Jing Zhang; Yanping Zhang; Ning Lv; Fen Li; Yibing Li; Zhenjie Guo (Environmental Research, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

Highly stable ultralong organic phosphorescence from a 3D organic supramolecule constructed by halogen bonding and π–π interactions - Aiping Yao; Jing Gao; Yingxiao Mu; Guangfu Li; Kuizhan Shao; Guogang Shan; Yun Geng; Yanping Huo; Zhongmin Su; Xinlong Wang (Chemical Engineering Journal, 2024)

Bacteria deploy water channels to aid infection in plants - Aziz Ul Ikram; Yanping Jing; Huan Chen; Jian Chen (Trends in Plant Science, 2024)

Characterization of a membrane Fcγ receptor in largemouth bass (Micropterus saloumoides) and its response to bacterial challenge - Jingya Wang; Jing Wu; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Fish Physiology and Biochemistry, 2024)

D-Limonene Alleviates Oxidative Stress Injury of the Testis Induced by Arsenic in Rat - Yanping Yang; Yan Hong; Jing Han; Zhe Yang; Nanmin Huang; Binwei Xu; Qi Wang (Biological Trace Element Research, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Vascular plant communities and biocrusts act as controlling factors in mitigating soil erosion on the Great Wall in a semi-humid area of Northwestern China - Yanping Liu; Rongliang Jia; Wanfu Wang; Yuchen Wan; Yanhong Gao; Hongtao Zhan; Jing Ren; Zhang Chen; Fei Qiu; Jing Zhu (Science of The Total Environment, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Online LC-ESI-MS/MS comparative analysis of N/O-glycopatterns in human colostrum from different ethnic groups in Northwest China - Xiaoqin Wang; Jing Liu; Shukai Wang; Yutao Xie; Yipei Liu; Jiangbo Fan; Yanping Li; Yu Lu; Linjuan Huang; Zhongfu Wang (Carbohydrate Polymers, 2024)

Measurement, influencing factors and prediction on carbon emission performance of countries along the Belt and Road - Jing Li; Yanping Zhou; Huiying Chen (Clean Technologies and Environmental Policy, 2024)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

Performance of production of polyhydroxyalkanoates from food waste fermentation with Rhodopseudomonas palustris - Tingxing Dan; Huiyan Jing; Tian Shen; Jia Zhu; Yanping Liu (Bioresource Technology, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Computer-aided engineering of CRISPR-Cas proteins for enhanced human genome editing - Yangcan Chen; Yanping Hu; Shengqiu Luo; Xinge Wang; Bangwei Mao; Yi Chen; Jing Xu; Zhikun Li; Qi Zhou; Wei Li (Science China Life Sciences, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

In situ transformation of bismuth-containing precursors into ultrathin bismuth nanosheets for enhanced electrochemical CO2 reduction - Aihao Xu; Dong Wei; Xiangyu Chen; Taishun Yang; Yanping Huang; Huibing He; Jing Xu (Chemical Engineering Journal, 2023)

Fcγ receptor‐mediated phagocytosis pathway was involved in phagocytosis of mIgM + B lymphocytes from largemouth bass ( Micropterus salmoides ) - Jing Wu; Yifan Nie; Jingya Wang; Guoqing Feng; Le Hao; Yanping Ma; Yugu Li; Zhenxing Liu (Journal of Fish Biology, 2023)
The potential for phagocytosis has been proven in teleost B cells, but the research on the regulatory mechanism of phagocytosis remains lacking. In this study, three largemouth bass ( Micropterus salmoides ) (15 ± 5 g) were injected intraperitoneally with Nocardia seriolae (10 5 CFU/100 μl/fish) in vivo , and their spleen was collected at 72 h post‐infection for mRNA‐seq. After the de novo assembly of the paired‐end reads, 73,622 unigenes were obtained. Gene expression profiling revealed that 2043 unigenes were differentially expressed after N. seriolae infection, comprising 1285 upregulated and 758 downregulated unigenes ( q ‐value 0.05, log2FC > |2|) of which 181 genes were involved in phagocytosis. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis demonstrated that 12 differentially expressed genes (DEG) associated with phagocytosis were enriched in the Fcγ receptor‐mediated phagocytosis signalling pathway. In vitro , the phagocytic ability of mIgM + B lymphocytes was validated using indirect immunofluorescence assay (IIFA) and fluorescence activating cell sorter (FACS), and the phagocytosis rates of the mIgM + B lymphocytes incubated with a Lyn inhibitor had decreased from 18.533 ± 6.00% to 11.610 ± 4.236% compared with the unblocked group. These results suggested that the Fcγ receptor‐mediated phagocytosis signalling pathway had participated in the phagocytosis of B cells and provide further insight into the role of B cells in innate immunology.

The impact of international technical cooperation in new energy industry on carbon emissions: evidence from the top 30 countries in the global innovation index - Huajie Xu; Yanping Zhou; Huiying Chen; Jing Li; Yuanyuan Kou (Environmental Science and Pollution Research, 2022)

The regulatory gene wblA is a target of the orphan response regulator OrrA in Streptomyces coelicolor - Yanping Zhu; Xinyuan Wang; Jing Zhang; Xue Ni; Xia Zhang; Meifeng Tao; Xiuhua Pang (Environmental Microbiology, 2022)
Summary Our previous study using transposon mutagenesis indicated that disruption of the putative response regulator gene orrA impacted antibiotic production in Streptomyces coelicolor . In this study, the role of OrrA was further characterized by comparing the phenotypes and transcriptomic profiles of the wild‐type S . coelicolor strain M145 and Δ orrA , a strain with an inactivated orrA gene. Chromatin immunoprecipitation using a strain expressing OrrA fused with FLAG showed that OrrA binds the promoter of wblA , whose expression was downregulated in Δ orrA . The interaction of OrrA with the wblA promoter was further validated by a pull‐down assay. Similar to Δ orrA , the deletion mutant of wblA (Δ wblA ) was defective in development, and developmental genes were expressed at similar levels in Δ orrA and Δ wblA . Although both OrrA and WblA downregulated actinorhodin and undecylprodigiosin, their roles in regulation of the calcium‐dependent antibiotic and yellow‐pigmented type I polyketide differed. sco1375 , a gene of unknown function, was identified as another OrrA target, and overexpression of either s co1375 or wblA in Δ orrA partially restored the wild‐type phenotype, indicating that these genes mediate some of the effects of OrrA. This study revealed targets of OrrA and provided more insights into the role of the orphan response regulator OrrA in Streptomyces .

Analysis and Health Risk Assessment of Potentially Toxic Elements in Three Codonopsis Radix Varieties in China - Ruibin Bai; Yanping Wang; Yajie Zhang; Yan Wang; Jiabing Han; Zixia Wang; Jing Zhou; Fangdi Hu (Biological Trace Element Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Levels of human cytomegalovirus miR-US25-1-5p and miR-UL112-3p in serum extracellular vesicles from infants with HCMV active infection are significantly correlated with liver damage - Jing Zhang; Yujing Huang; Qing Wang; Yanping Ma; Ying Qi; Zhongyang Liu; Jingui Deng; Qiang Ruan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Characterization of eleven microsatellite markers for the tea geometrid Ectropis obliqua (Lepidoptera: Geometridae) - Shengli Jing; Baoxiao Zheng; Li Qiao; Kun Zhang; Gaoyang Chen; Shunqin Guo; Xiaoyan Huang; Yanping Gao; Lili Zhang; Hongyu Yuan (Applied Entomology and Zoology, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Extracellular ATP is involved in the initiation of pollen germination and tube growth in Picea meyeri - Junhui Zhou; Chengyu Fan; Kai Liu; Yanping Jing (Trees, 2015)

Genetic diversity and demographic history of the endangered and endemic fish (Platypharodon extremus): implications for stock enhancement in Qinghai Tibetan Plateau - Junhu Su; Weihong Ji; Yanping Zhang; Dianne M. Gleeson; Zhongyu Lou; Jing Ren; Yanming Wei (Environmental Biology of Fishes, 2015)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Growth and yield of oleic sunflower (Helianthus annuus L.) under drip irrigation in very strongly saline soils - Shuqin Wan; Yanping Jiao; Yaohu Kang; Shufang Jiang; Junli Tan; Wei Liu; Jing Meng (Irrigation Science, 2013)

Reference gene selection for qPCR in Ammopiptanthus mongolicus under abiotic stresses and expression analysis of seven ROS-scavenging enzyme genes - Jing Shi; Meiqin Liu; Junna Shi; Guangshun Zheng; Yanping Wang; Jinyu Wang; Yuzhen Chen; Cunfu Lu; Weilun Yin (Plant Cell Reports, 2012)

Preliminary assessment of heavy metal contamination in surface water and sediments from Honghu Lake, East Central China - Ying Hu; Shihua Qi; Chenxi Wu; Yanping Ke; Jing Chen; Wei Chen; Xiangyi Gong (Frontiers of Earth Science, 2012)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)